Nondestructive Prediction of Oil Palm Fruit Quality During Processing Delays Using Electrical Impedance Spectroscopy - Arief Al Akbar; I Wayan Budiastra; Irmansyah Irmansyah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Nondestructive prediction of palm fruit quality is needed to monitor changes in palm fruit quality during processing delays. This study aims to develop a method for predicting the chemical quality of palm fruit during processing delays using the Electrical Impedance Spectroscopy (EIS). The electrical impedance of palm fruit were measured at frequencies of 50 Hz to 1 MHz and followed by the determination of free fatty acid (FFA) and moisture content using chemical methods. The best initial treatment for impedance spectrum data in this study was Standard Normal Variate (SNV) and Baseline. The results of this study indicate that the PLS method outperforms PCR in predicting FFA and moisture content. The best prediction for free fatty acid content was using the SNV pre-treatment and component factor 7 with a value of r = 0.87; SEC = 2.75%; SEP = 2.82%; CV = 23.81%; RPD = 1.94 and consistency of 97.75%. The best prediction for moisture content was obtained using the Baseline initial treatment and component factor 15 with a value of r = 0.97; SEC = 3.65%; SEP = 3.82%; CV = 28.24%; RPD = 1.91 and consistency of 83.24%. The developed electrical impedance and PLS methods can be used to predict free fatty acid content and moisture content of oil palm fruit during processing delays.